2009 Influenza A (H1N1) in Panama: a disease affecting children with a benign course - Javier Nieto- Guevara; Nestor Sosa; Mariana Garcia; Alex Martinez; Marlene Castillo (Journal of Infection in Developing Countries)
Introduction: Pandemic Influenza A (H1N1) was identified as the major febrile respiratory illness worldwide during the year 2009.  We present a report of its clinical and epidemiological characteristics in children and adults in Panama.